The Readiness of Health & Computer Science Faculties Graduates in This Industrial Revolution 4.0 Related to English Communicative Competence (Case study at Duta Bangsa University 2019) - Ratini Setyowati; Beta Setiawati (Proceeding of International Conference on Science, Health, And Technology, 2019)
One of the phenomena in Industrial Revolution 4.0 is common digitization and ensuring constant communication between people themselves, people and devices and between devices themselves. Therefore in this Industrial revolution 4.0 or Destruction era, English Communicative Competence is one of the important skills. Based on Tracer Study of Duta Bangsa University, alumni’s English Communicative Competence has not been satisfied. The objectives of the research are to know whether the graduates are ready or not to face the Industrial Revolution 4.0?. This research used descriptive qualitative method. The research used TOEIC that was tested by International Test Center (ITC) to know the result of the research. The populations of the research were the entire students who would graduate in the academic years 2018/2019, there were 308 students from Health Faculty anda 176 students from Computer Science faculty. The researchers used TOEIC to know the English Communicative Competence of Health and Computer Science faculty graduates. The results from TOEIC showed that the higher TOEIC score was 955 (International Proficiency), the minimum score was 140 (No Useful Proficiency) and the mean score was 288 (Elementary Proficiency). It means that most of the students have not been ready to competate in this era and the graduates needs good English Communicative Competence to competate in this distruction era.